Information System Point of Sales Based Real Time on PT. Buccheri Indonesia - Teofilus Sunarsa; Paulus Yayan Christian; Yuki Gunawan (bit-Tech, 2020)
Buccheri is a retail company that provides quality footwear for men and women since 1980. We begin our history with our first flagship store in a historic business district, "Pasar Baroe." Now Buccheri has been through various challenges and experienced many developments. This of the most prestigious and footwear brand in Indonesia. As the leading formal shoes in Indonesia, Buccheri tends to put their segmentation in the middle-upper class. Established in 1980, the name of this brand is well known among Indonesian consumers. With specialized informal to daily leather-based footwear, and claimed as a handcrafted, stylish yet comfortable footwear brand. Buccheri is committed to providing a high-quality product and post-buying service and maintaining the best craftsmanship in every item that we produce. Innovation is also one of the keys to our future development. With the development of existing technology, Buccheri made changes to its sales system. With the many stores that exist, real-time technology is needed to meet the company's business needs. Therefore, the point of Sale is redeveloped to answer the needs of time-based